Institucionalidade e espacialidade da defesa nacional na Amazônia: perspectivas para o Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Even with a history of friendly relations with neighbor countries, the Brazilian government perceived threats to its national sovereignty and, in different historical moments, had to worry about defense matters, formulating policies both inside and outside the military institutions in order to keep the territorial integrity and safeguard resources and national interests. The perception of the need to defend the Amazonian frontiers was a historical construction that underwent a process of institutionalization and spatialization and generated the formal justification for the creation of the former Federal Territories, as was the case of the formation of the state of Amapá. Based on the question of whether the institutionalization in the field of defense (creation of actors and systematization of official policy and strategy documents) were accompanied by spatialities in the Amazon region, and especially in the state of Amapá, capable of guaranteeing national defense as a problem, the main goal of this work was to make a study on the institutionalization and the spatialization of the national defense in the Amazonian context with a focus on the state of Amapá. This dissertation made a study that privileged the qualitative analysis based on the hypothetical-deductive method and the use of the bibliographic review as research techniques, always starting from the official perception of the institutionalization and the spatialization to later do an analysis of the theme. The dissertation concludes with the observation that the binomial institutionalization-spatialization of national defense when observed from the point of view of the Amazon region in general, and Amapá in particular, will reveal a different reality from that one built by the official discourses founded in the National Defense Policy and in the National Defense Strategy. Although Amazonia and Amapá are seen as geopolitically strategic spaces, spatialities that arose from institutionalizations that were in harmony with the discourse of importance of the Amazon region do not seem to be able to fully protect the national resources and guarantee sovereignty
Keywords: Defesa Nacional; Forças Armadas; Fronteiras; Amazônia; Amapá (Estado); CNPQ::CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA POLITICA; DESENVOLVIMENTO E PLANEJAMENTO SOCIOECONÔMICO; MEIO AMBIENTE, CULTURA E DESENVOLVIMENTO REGIONAL